The development of an electronic system for contracts and the execution of building work in Germany - Schieg, Martin (Business: Theory and Practice, 2006)
Public administrations are banking on electronic media to improve their processes, particularly in the field of construction due to the potential savings that are expected. With the project e-system for the award of public contracts the federal government is pursuing the aim of handling public procurement entirely over the internet. The legal requirements have been created in the form of the Digital Signatare Act (Signaturgesetz) and the corresponding changes in the Regulations on Provisions for the Award of Public Contracts and the Official Contracting Terms for the Award of Contracts. The focus is on making legally binding declarations on intent. This is made possible by the advanced electronic signature with a qualified certificate. In technical terms the concept is realised through the use of a public key concept. In Germany, the electronic system for the award of public contracts has been implemented in the context of three pilot projects which are explained in the study.